Predictive role of capillaroscopic skin ulcer risk index in systemic sclerosis: a multicentre validation study. Issue 1 (13th September 2011) - Sebastiani, M; Manfredi, A; Vukatana, G; Moscatelli, S; Riato, L; Bocci, M; Iudici, M; Principato, A; Mazzuca, S; Del Medico, P; De Angelis, R; D'Amico, R; et al.
Abstract : Introduction: The early detection of systemic sclerosis (SSc) patients at high risk of developing digital ulcers could allow preventive treatment, with a reduction of morbidity and social costs. In 2009, a quantitative score, the capillaroscopic skin ulcer risk index (CSURI), calculated according to the formula 'D×M/N 2', was proposed, which was highly predictive of the appearance of scleroderma digital ulcers within 3 months of capillaroscopic evaluation. Objectives: This multicentre study aims to validate the predictive value and reproducibility of CSURI in a large population of SSc patients. Methods: CSURI was analysed in 229 unselected SSc patients by nailfold videocapillaroscopy (NVC). All patients were re-evaluated 3 months later with regard to the persistence and/or appearance of new digital ulcers. Results: 57 of 229 patients presented with digital ulcers after 3 months. The receiver operating characteristic curve analysis showed an area under the curve of 0.884 (95% CI 0.835 to 0.922), with specificity and sensitivity of 81.4% (95% CI 74.8 to 86.89) and 92.98% (95% CI 83.0 to 98.0), respectively, at the cut-off value of 2.96. The reproducibility of CSURI was validated on a random sample of 81 patients, with a κ-statistic measure of interrater agreement of 0.8514. Conclusions: The role of CSURI was confirmed in detecting scleroderma patients with a significantly high risk of developing digital ulcers within the first 3 months from NVC evaluation. CSURI is the only method validated to predict the appearance of digital ulcers and its introduction into routine clinical practice might help optimise the therapeutic strategy of these harmful SSc complications.